Originally Posted by

**JohnnyB** trying to differentiate:

$\displaystyle 1-x^2 / (x^2+1)^2$

using the quotient rule,

$\displaystyle u = (1-x^2)$

$\displaystyle du/dx = -2x$

$\displaystyle v = (x^2+1)^2)$

$\displaystyle dv/dx = 4x(1+x^2)$

$\displaystyle [u * dv/dx ] - [v *du/dx] / v^2$

I've been given an answer to complete working out to:

$\displaystyle 2x(x^2-3)/(x^2+1)^3$

I've managed to work it out up to

$\displaystyle 2x(x^2-1)/(x^2+1)^3$

but have no idea where the 3 in the the provided answer came from